2014
DOI: 10.1016/j.eplepsyres.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Tractography of Meyer's Loop asymmetries

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Tractography of meyer's loop asymmetries NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21272153&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21272153&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
4
16
0
Order By: Relevance
“…Specifically, we find left-ward asymmetry of the optic radiation. This is consistent with post-mortem study results that also found the optic radiation was larger on the left hemisphere on a sample size of 10 (Dreessen de Gervai et al 2014). Our results provide an in vivo validation of this finding on a large HCP cohort.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, we find left-ward asymmetry of the optic radiation. This is consistent with post-mortem study results that also found the optic radiation was larger on the left hemisphere on a sample size of 10 (Dreessen de Gervai et al 2014). Our results provide an in vivo validation of this finding on a large HCP cohort.…”
Section: Discussionsupporting
confidence: 91%
“…The final bundle was formed by combining the components, but the typical final product obtained in that study did not form the expected continuous sheet representation of the optic radiation. Asymmetry of the left and right Meyer’s loop was studied by Dreessen de Gervai et al (2014) with the probabilistic tractography tool in MedINRIA (Fillard et al , 2007) on a cohort of 20 healthy subjects. Three sub-bundles of the optic radiation were computed separately with different inclusion ROIs that were manually placed around the LGN.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high anatomical variability and marked asymmetry that is associated with the distance of Meyer's Loop to the temporal pole between hemispheres (Bürgel et al, 2006;Jeelani et al, 2010;Dreessen de Gervai et al, 2014), in this study we were able to successfully map the optic radiation in all subjects. In particular, we were able to do so in a pediatric surgical cohort and show, to the best of our knowledge, the first report that relates the degree and location of resection extent with optic radiation involvement in a pediatric surgical series.…”
Section: Clinical Correlations With Tractographymentioning
confidence: 77%
“…Nevertheless, having lateralised results are not surprising: several studies showed asymmetric function and structure in the visual system (Antal et al, 2004;Dreessen de Gervai et al, 2014).…”
Section: Discussionmentioning
confidence: 91%